Kinetic studies of C1 and C2 Criegee intermediates with SO2 using laser flash photolysis coupled with photoionization mass spectrometry and time resolved UV absorption spectroscopy. Issue 34 (17th August 2018) - Howes, N. U. M.; Mir, Z. S.; Blitz, M. A.; Hardman, S.; Lewis, T. R.; Stone, D.; Seakins, P. W.
Abstract : Kinetics of CH2 OO + SO2 confirmed over a wide range of [SO2 ]. Acetaldehyde observed as a major product of the reaction of CH3 CHOO + SO2 . Abstract : Recent, direct studies have shown that several reactions of stabilized Criegee intermediates (SCI) are significantly faster than indicated by earlier indirect measurements. The reaction of SCI with SO2 may contribute to atmospheric sulfate production, but there are uncertainties in the mechanism of the reaction of the C1 Criegee intermediate, CH2 OO, with SO2 . The reactions of C1, CH2 OO, and C2, CH3 CHOO, Criegee intermediates with SO2 have been studied by generating stabilized Criegee intermediates by laser flash photolysis (LFP) of RI2 /O2 (R = CH2 or CH3 CH) mixtures with the reactions being followed by photoionization mass spectrometry (PIMS). PIMS has been used to determine the rate coefficient for the reaction of CH3 CHI with O2, k = (8.6 ± 2.2) × 10 −12 cm 3 molecule −1 s −1 at 295 K and 2 Torr (He). The yield of the C2 Criegee intermediate under these conditions is 0.86 ± 0.11. All errors in the abstract are a combination of statistical at the 1 σ level and an estimated systematic contribution. For the CH2 OO + SO2 reaction, additional LFP experiments were performed monitoring CH2 OO by time-resolved broadband UV absorption spectroscopy (TRUVAS). The following rate coefficients have been determined at room temperature ((295 ± 2) K):CH2 OO + SO2 : k = (3.74 ± 0.43) × 10 −11 cm 3 molecule −1 s −1 (LFP/PIMS), k = (3.87 ± 0.45) × 10 −11 cm 3 molecule −1 s −1 (LFP/TRUVAS) CH3 CHOO + SO2 : k = (1.7 ± 0.3) × 10 −11 cm 3 molecule −1 s −1 (LFP/PIMS) LFP/PIMS also allows for the direction observation of CH3 CHO production from the reaction of CH3 CHOO with SO2, suggesting that SO3 is the co-product. For the reaction of CH2 OO with SO2 there is no evidence of any variation in reaction mechanism with [SO2 ] as had been suggested in an earlier publication (Chhantyal-Pun et al., Phys. Chem. Chem. Phys., 2015, 17, 3617). A mean value of k = (3.76 ± 0.14) × 10 −11 cm 3 molecule −1 s −1 for the CH2 OO + SO2 reaction is recommended from this and previous studies. The atmospheric implications of the results are briefly discussed.